Application of Law by Judges to Family Neglect Reviewed from a Criminal Law Perspective - Wahyuni, Sry; Fauzi, Engrina; Fiona, Fera (Jurnal Ilmiah Ekotrans & Erudisi, 2024)
Domestic neglect is a serious offense that harms family members who depend on the abuser to meet their basic needs. Law Number 23 of 2004 concerning the Elimination of Domestic Violence (UU PKDRT) regulates this action in Indonesian criminal law. To uphold justice and provide protection to victims, judges must apply the law against perpetrators of domestic neglect. In this article, we focus on the judicial process, the imposition of prison sentences, and the impact of the judge's decision on family neglect from a criminal law perspective. The judge examines evidence and witness statements thoroughly during the trial process to ensure that all elements of the criminal act of neglect are met. The aim of imposing a prison sentence is to punish the perpetrator, protect the victim from threats, and uphold justice. However, imposing a prison sentence can also have negative impacts on victims, including economic, psychological and social pressure. To reduce these negative effects, mitigation measures are needed which include economic assistance, psychological support, child protection, education and public awareness, as well as rehabilitation of perpetrators. To do this, governments, local communities and non-governmental organizations (NGOs) must work together. As a result, judges can take effective legal action against perpetrators of domestic neglect, providing justice, and ensuring that victims are protected and rehabilitated as best as possible.